(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
The variations for 6-14-year-old India children in primary school enrollment by gender across three socioeconomic divisions, namely bottom and top caste Hindus, and Muslims, are described and analyzed in this study. It also looks at how inter-community and gender disparities evolved throughout the 1990s decade. India saw extraordinary economic development during this decade, and overall enrollment rates soared. The amount of information on how social disparities evolved throughout this time period is still minimal. This study examines this using data from The National Family Health Survey (NFHS) was conducted twice, with 108,899 youngsters in 1992/3 and 104,714 children in 1998/9. The consumer durables index is based on owning twelve different items like a refrigerators or a motorbike. High caste Hindus have more daily necessities and land than that of the other two groups, with Muslims having minimal land and lesser caste Hindus having the fewest durables.